Respostas

2013-10-02T16:54:36-03:00
(3x² - 5x + 2) + ( x² + 6x  - 4) +( 5x - 7)    tira dos parenteses fazendo o jogo dos sinais
=3x² -  5x + 2   + x² + 6x  - 4 + 5x - 7       e vai agrupando os termos iguais para se  
=3x² + x² + 6x  +5x -5x - 7 - 4 +2             se resolver
= 4x² +11x - 5x - 11 +2
= 4x² + 6x - 9

2y - [ - 3xy + ( -2x + 5y) - (  - 4 xy + x) ]
= 2y - [ - 3xy - 2x + 5 y + 4xy - x ]
= 2y + 3xy + 2x - 5y - 4xy + y
= 3xy - 4xy - 5y + 2y + 2x +x
= - xy - 3y + 3x

( 5x² + 3ax  - a²  ) - ( 5ax   - a²) + ( 3ax  - x²)
= 5x² + 3ax - a²  - 5ax + a² + 3ax  - x²
= 5x² - x² + 3ax - 5ax  + 3ax + a² - a²         
= 4x² +6ax -  5ax
= 4x² + ax
1 5 1